PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN BERBANTUAN MEDIA KARTU KATA SISWA KELAS 1 SDN NGAGELREJO 1/396 SURABAYA - Isma Mulia Alifiana; Putri Zuroidah; Nurma Iktamalannisa; Mundiroh; Mutiara Nikmah; Jauharotul Lailia; Ira Eko Retnosari; Juanita Purnama Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading skills are a fundamental aspect of basic education that plays an important role in students' academic development. However, according to the results of observations in class 1C of SDN Ngagelrejo 1/396 Surabaya, it is known that the majority of students experience challenges in reading basicly. Therefore, creative learning methods are needed to improve students' reading skills. The focus of this study is to improve the early reading ability of grade 1C students at SDN Ngagelrejo 1/396 Surabaya by utilizing word card media. This study applied a classroom action research method based on the Kemmis and McTaggart models, which included the planning phases, implementation of actions, observation, and reflection applied in two cycles. The study subjects consisted of 28 students who were selected according to the results of observations and preliminary tests that showed the need for improvement in reading ability. Data is collected through testing, observation, and documentation. The findings of the study indicate that the application of card media in a structured and intensive manner has a positive impact on improving students' reading skills. In the pre-action, only 42.86% of students obtained an average score but after cycle II, the figure increased to 85.71%. In addition, students' reading ability experienced an increase in average score from 67.25 in the pre-action to 83.21 in the second cycle. This improvement indicates that word cards as an attractive learning medium and supported by intensive teacher guidance can effectively improve students' initial reading skills.